Improving critical thinking skills of English language learners in middle schools (Eurasian Scientific Herald, 2022)
The article deals with critical thinking and its usage in English lessons. The author analyses the advantages of using critical thinking activities in FLT and also gives the ways of improving the critical thinking skills of the school students.